Regional Foreign Policy of the Republic of Uzbekistan in the Context of Globalization and the Factors Affecting It (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article examines the regional foreign policy of the Republic of Uzbekistan in the context of globalization, focusing on the military-political situation and the various factors influencing it. The author discusses Uzbekistan's proactive approach to establishing strong, mutually beneficial relationships with neighboring Central Asian countries, prioritizing regional security and stability, particularly in relation to Afghanistan. The article highlights key elements of Uzbekistan's Defense Doctrine, emphasizing the importance of maintaining military readiness and addressing threats such as terrorism, extremism, and cross-border crimes. Additionally, it explores the broader implications of globalization on the region's security, the role of international cooperation, and the importance of developing national armed forces in Central Asia. The challenges posed by external and internal risks, as well as the strategic responses proposed by Uzbekistan, are also analyzed. The article underscores the significance of Uzbekistan's foreign policy in promoting regional peace and stability, while navigating the complex dynamics of globalization.